Digital-Based Maritime Tourism Development Policy in the Anambas Islands in maintaining Maritime Sovereignty - Khairina, Etika; Karol Teovani Lodan; Lubna Salsabila (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
The Anambas Archipelago, one of the potential areas for marine tourism in Indonesia, is located in the Riau Archipelago. Supported by a strategic location, being on the path of New Regional development, becoming an international shipping lane and directly adjacent to the State of Singapore. This study aims to look at the policy of developing digital-based marine tourism in the Anambas Islands. This study uses a qualitative method. Source of data obtained from primary data, secondary data. Observation data collection techniques, interviews, documentation, FGD. Triangulation data analysis technique assisted by N-Vivo12Pluss Tools. Maritimetourism development policy is seen from three aspects, namely the policy of compiling E-Tourism prototypes, developing tourist attractions, developing promotion/marketing of marine tourism. The results of the Anambas Islands Regency government have not been optimal in developing digital-based marine tourism. Even though the government already has a National Tourism Development Master Plan (RIPPARNAS) for 2010-2025, which is directed at the development of maritime tourism, there are no specific steps or tourism development policies that carry a digital approach. Based on the theory used, it is known that tourists' needs for accessibility where information access facilities must be easily achieved and technology supporting facilities such as telecommunications and internet access which are added so as to satisfy tourists using technology and smartphones when traveling in Anambas have not been fully realized. So that the role of digital in the marine tourism of the Anambas Islands has not fully provided a positive influence while digitalization should add excellence to the tourist experience.